Using Bar Velocity to Assess Post-match Neuromuscular Fatigue in Young Soccer Players - Barreira, João; Gantois, Petrus; Castro, Jorge; Mesquita, Xavier; Peixoto, Rafael; Cid, Miguel Ferreira; Loturco, Irineu; Sousa, Ana; Nakamura, Fábio Yuzo (International Journal of Sports Medicine, 2024)
This study aimed to investigate the recovery of neuromuscular performance using mechanical parameters collected during jump (vertical and horizontal) and strength-power exercises in youth soccer players after official soccer matches. Twenty-one outfield highly trained youth male soccer athletes (age: 18.23±0.73 years; weight: 72.12±6.99 kg; height: 1.78±0.08 m) from two teams competing in the 1st division of U-19 Portuguese National Championship participated in this study. Players completed a battery of physical tests at −2 h, + 30 min, +24 h, and +48 h in relation to the match. Countermovement jump height, horizontal jump distance, and bar velocity during the half squat, bench press, and hip thrust exercises, at fixed loads, were recorded. Countermovement jump was impaired until 24 h post-match (−1.7% from pre- to 24 h post-match, p=0.050; ES=−0.82). Half-squat bar velocity was reduced immediately following the match (−6.8% from pre-match, p=0.004; ES=−0.64) but recovered at +24 h (+2.9%, p=1.00; ES=0.02). Hip-thrust bar velocity was reduced for up to 48 h post-match (−7.4% from pre- to 48 h post-match, p<0.001; ES=−0.80). No impairments were found in the horizontal jump and bench press at any moment. Our findings show prolonged decrements in strength of the posterior chain following a soccer match, measured in the hip thrust exercise, while the other exercises displayed faster recovery dynamics.
Keywords: fatigue; recovery; team sports; strength training